БАДИИЙ ҲАҚИҚАТ ВА МУАЛЛИФ МУНОСАБАТИ (Scientific journal of the Fergana State University, 2023)
On the basis of analysis novels “Face to face” and “Jamila” by Chingiz Aitmatov  writer’s skill to reveal  inner world of the characters’ are uncovered in this article. Search for raising reality of life to artistic reality level is widely studied.